Using existing network infrastructure to estimate building occupancy and control plugged-in devices in user workspaces. (1st January 2014) - Christensen, Ken; Melfi, Ryan; Nordman, Bruce; Rosenblum, Ben; Viera, Raul
Buildings are a major consumer of energy. We believe that energy can be saved with the notion of implicit occupancy sensing where existing IT infrastructure can be used to replace and/or supplement explicit dedicated sensors to determine building occupancy and drive building operation. Implicit sensing has the promise to be both lower in cost than explicit sensing based on PIR and ultrasound sensors and to offer additional useful data about the occupants of a building. Our implicit sensing methods are largely based on monitoring IP and MAC addresses in Wi-Fi access points and in routers, and then correlating these addresses to the occupancy of a floor, area, or room of a building. We experimentally evaluate the feasibility of this dual-use of IT infrastructure. We demonstrate an application of implicit sensing to sense the pending occupancy of a user workspace and automatically control the plugged-in devices in the workspace.